Falls among Brazilian older adults living in urban areas: ELSI-Brazil - Wendel Rodrigo Teixeira Pimentel; Valéria Pagotto; Sheila Rizzato Stopa; Maria Cristina Corrêa Lopes Hoffmann; Fabíola Bof de Andrade; Paulo Roberto Borges de Souza Junior; Maria Fernanda Lima-Costa; Ruth Losada de Menezes (Revista de Saúde Pública, 2018)
ABSTRACT OBJECTIVE To assess the prevalence and factors associated with falls in a nationally representative sample of older Brazilians residing in urban areas. METHODS Data from 4,174 participants (60 years or older) from the baseline of ELSI-Brazil, conducted between 2015 and 2016, were used. The outcome variable was the reporting of one or more falls in the last 12 months. The exploratory variables were sociodemographic characteristics, factors related to the urban environment, and health conditions. Statistical analysis was performed using Poisson regression. RESULTS The prevalence of falls was 25.1%. Of these, 1.8% resulted in a hip or femur fracture and, among them, 31.8% required surgery for prosthesis placement. Statistically significant associations (p < 0.05) with falls were observed for females [prevalence ratio (PR) = 1.26], age group of 75 years or older (PR = 1.21), fear of falling due to defective sidewalks (PR = 1.47), fear of crossing streets (PR = 1.22), diabetes (PR = 1.17), arthritis or rheumatism (PR = 1.29), and depression (PR = 1.53). No significant associations were found for educational level, marital status, hypertension, and perception of violence in the neighborhood. CONCLUSIONS The factors associated with falls among older adults are multidimensional, comprising individual characteristics and the urban environment, which indicates the need for intra and intersectoral actions to prevent falls in this population.